Evaluation of a solar drying system for kaolin processing: polycarbonate coating x polypropylene coating - Santana, Vitor Leão (2021)
This work aimed to contribute to the evaluation of a solar drying system used in the drying of kaolin, which is under development in the region of the Pegmatitic Province of Borborema (PPB), between the states of Paraíba and Rio Grande do Norte. The experiments were carried out in a direct exposure solar dryer and outdoor solar drying. Two prototype dryers with different types of coverage were tested, one with a polycarbonate coating and the other with a polypropylene coating, to evaluate the influence of the transparent coating on the efficiency of the drying process. A comparison was also made between the two dryers and outdoor solar drying, evaluating the drying time of kaolin and the thermal efficiency of the equipment. The amount of water removed from the kaolin per unit of time and the specific energy consumption were other indicators evaluated for each drying process, and were important to corroborate the need to use new drying technologies in the PPB region, which has high intensity incident solar irradiation throughout the year, but which still uses firewood as energy source to carry out the drying step in the kaolin processing. The main experimental results obtained showed that solar drying in the dryers reduced kaolin moisture from 30% to 5%, leaving it in a position to proceed to the next processing step, 240 minutes faster compared to solar air drying free. It was already possible to observe that the solar dryer with polycarbonate cover proved to be more thermally efficient compared to the dryer with polypropylene cover. New experiments are being carried out seeking to insert solar energy as a major energy source, replacing firewood and aiming to improve the efficiency of the drying process and give sustainability to the kaolin processing actions in the PPB region.